Targeted Delivery for Cardiac Regeneration: Comparison of Intra-coronary Infusion and Intra-myocardial Injection in Porcine Hearts - Vekstein, Andrew M.; Wendell, David C.; DeLuca, Sophia; Yan, Ruorong; Chen, Yifan; Bishawi, Muath; Devlin, Garth W.; Asokan, Aravind; Poss, Kenneth D.; Bowles, Dawn E.; Williams, Adam R.; Bursac, Nenad (Frontiers in Cardiovascular Medicine, 2022)
Background: The optimal delivery route to enhance effectiveness of regenerative therapeutics to the human heart is poorly understood. Direct intra-myocardial (IM) injection is the gold standard, however, it is relatively invasive. We thus compared targeted IM against less invasive, catheter-based intra-coronary (IC) delivery to porcine myocardium for the acute retention of nanoparticles using cardiac magnetic resonance (CMR) imaging and viral vector transduction using qPCR. Methods: Ferumoxytol iron oxide (IO) nanoparticles (5ml) were administered to Yorkshire swine (n=13) by: 1) IM via thoracotomy, 2) catheter-based IC balloon-occlusion (BO) infusion into the distal left anterior descending (LAD) coronary artery, 3) IC balloon occlusion with perforated side-wall (SW) infusion into the LAD, or 4) non-selective IC via left main (LM) coronary artery infusion. Hearts were harvested and imaged using at 3T whole-body MRI scanner. In separate Yorkshire swine (n=13), an adeno-associated virus (AAV) vector was similarly delivered, tissue harvested 4-6 weeks later, and viral DNA quantified from predefined areas at risk (apical LV/RV) versus not at risk in a potential mid-LAD infarct model. Results were analyzed using pairwise Student’s t-test. Results: IM delivery yielded the highest IO retention (16.0±4.6% of left ventricular volume). Of the IC approaches, BO showed the highest IO retention (8.7±2.2% vs. SW=5.5±4.9% and LM=0%) and yielded consistent uptake in the porcine distal LAD territory, including the apical septum, LV, and RV. IM delivery was limited to the apex and anterior wall, without septal retention. For the AAV delivery, the BO was most efficient in the at risk territory (Risk: BO=6.0x10-9, IM=1.4x10-9, LM=3.2x10-10 viral copies per µg genomic DNA) while all delivery routes were comparable in the non-risk territory (BO=1.7x10-9, IM=8.9x10-10, LM=1.2x10-9). Conclusions: Direct IM injection has the highest local retention, while IC delivery with balloon occlusion and distal infusion is the most effective IC delivery technique to target therapeutics to a heart territory most in risk from an infarct.